2011
DOI: 10.1016/j.ijcard.2010.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Impact of statin use on heart failure mortality

Abstract: Veterans who were not exposed to statin therapy at any time during the study period were 1.56 times more likely to suffer all-cause mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 29 publications
2
23
0
Order By: Relevance
“…In addition, down-regulation of the SERCA2 activity by 26.4 % (p < 0.05) was observed (Table II). Previous studies have shown that statins can restore heart function in ischemic or non-ischemic cardiomyopathy (8,11), ameliorate BNP up-regulation (10), down-regulate arrhythmic events (6) and reduce sudden cardiac death (21) in addition to their lipid--lowering effects. Our present study also demonstrated that pitavastatin could ameliorate cardiac malfunction in DCM mice, especially in the high dose group (p < 0.05) (Figs.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, down-regulation of the SERCA2 activity by 26.4 % (p < 0.05) was observed (Table II). Previous studies have shown that statins can restore heart function in ischemic or non-ischemic cardiomyopathy (8,11), ameliorate BNP up-regulation (10), down-regulate arrhythmic events (6) and reduce sudden cardiac death (21) in addition to their lipid--lowering effects. Our present study also demonstrated that pitavastatin could ameliorate cardiac malfunction in DCM mice, especially in the high dose group (p < 0.05) (Figs.…”
Section: Resultsmentioning
confidence: 99%
“…Heart failure was most consistently associated with all types of lipid abnormalities independent of statin treatment. Several observational studies have shown statins to be associated with reduced mortality in patients with heart failure [25]; while some randomized controlled statin trials have shown a reduction in hospitalization and improved markers [26,27,28,29], they have not demonstrated mortality in this patient population [27,29]. Factors associated with mortality in patients with heart failure are complex and are beyond the scope of this observational study.…”
Section: Discussionmentioning
confidence: 99%
“…We have greatly enjoyed reading the recently published letter by Topatan and Başaran [1] related with CA-125 and heart failure. In this report, the authors commented on an article related with the prognostic value of CA-125 in patients with advanced heart failure [2].…”
Section: Dear Editormentioning
confidence: 99%
“…Besides, in the study of Yilmaz et al [4], patients with high CA-125 levels were shown to have more frequent hospitalization and mortality. Although, in the manuscript [1], the authors primarily focused on the mesothelium as the primary source of CA-125, from recent articles [5][6][7][8][9][10], we have learned a lot about the pathophysiological link of CA-125 in heart failure. CA-125 levels were shown to be related with the serum TNF-alpha, IL-6 and IL-10 levels, and hence pathobiological link might possibly be driven through cytokines [9].…”
Section: Dear Editormentioning
confidence: 99%
See 1 more Smart Citation